Prediction of blast furnace hearth condition: part II – a transient state simulation of hearth condition during blast furnace shutdown. (27th May 2020) - Dong, X. F.; Zulli, P.; Biasutti, M.
ABSTRACT: The extent of hearth cooling is critically important in determining the feasible duration of an extended blast furnace maintenance shutdown. Based on a fixed domain method, a transient numerical model has been developed which considers the effect of solidification enthalpy of liquid iron in a coke-free bath, enabling the progress of hearth cooling to be monitored. The model was initially verified by comparing calculations with actual refractory temperatures during shutdowns of shorter duration (typically 1–2 days) at BlueScope's No. 5 Blast Furnace. It was then applied to estimate the hearth condition during an extended shutdown period (typically, 5–6 days). The calculated refractory temperature differences were reasonably matched with the measured data over the extended shutdown period. This allowed visualization of the temporal variation of refractory temperatures and the extent of liquid bath cooling during extended shutdowns, providing useful guidance for furnace engineers.